Persepsi terhadap Peringatan Kesehatan Bergambar pada Bungkus Rokok dan Perilaku Merokok Remaja di Yogyakarta - Heni Trisnowati; oktavianus Emildus Nabut; Utari Marlinawati (Faculty of Public Health, Faculty of Medicine and Health, Universitas Muhammadiyah Jakarta, 2018)
Background: The prevalence of teenage smokers increase steadily in Indonesia. The Government issued Government Regulation No. 109 of 2012 on the Security of Ingredient-Containing Addictive Substances in the form of Tobacco Products For health and the implementation of pictorial health warning on cigarette packaging has been enforced since July 2014 to overcome it. Objective: To know the relationship of perception forwad pictorial health warning (PHW) with smoking behavior of adolescents who are incorporated in the Manggarai Raya Yogyakarta Family Association (IKAMAYA). Method: This research used explanatory research design. Respondents were IKAMAYA teenagers totaling 145 people. Data collection with questionnaire then analyzed by univariat and bivariat. Result: The five PHW are considered very helpful in reminding smokers to quit smoking or reduce smoking habits. The number of male adolescents who smoked 37.2% while the number of adolescent girls who smoked 6.9%. There is a significant correlation between adolescent perception toward five PHW with adolescent smoking behavior. P value respectively from p1-p5 (0,039; 0,001; 0,025; 0,022; 0,027). Conclusion: Pictorial Health Warning on cigarette packing effective in reducing smoking habit of adolescents. Respondents who have positive perceptions forwad PHW tend to reduce cigarette consumption, whereas respondents who have negative perception of PHW tend to remain smoking behavior.Keywords: Perception, Pictorial Health Warning, smoking behavior, adolescent